Makna Tarian Jubata Suku Dayak Kanayatn dalam Perspektif Aspek dan Nilai Transendental - Nikodemus, Nikodemus; Fangalanso, Chandida (Balale' : Jurnal Antropologi, 2023)
The focus of writing this scientific work is examining the meaning of the Jubata Dance of the Dayak Kanayatn Tribe in the Transcendental Aspect Perspective as its scalpel. The purpose of writing a scientific paper is first of all to examine more deeply the meaning of spirituality contained in the Jubata Dance of the Kanayatn Dayak Tribe. The Jubata Dance is a Dayak Kanayatn tradition to express human life on earth. Before the development of technology and communication, the Dayak Kanayatn people showed their lives through dances that contained the meaning of life. In this article the writer uses descriptive method. Apart from book sources, the author interviewed several sources or local people who pay attention to culture (traditional leaders), especially traditional leaders. What has been obtained in this scientific work is finding the values of human life in culture, especially in the cultural arts of the Jubata Dance. The Jubata Dance is believed by the Dayak people as a traditional healing ceremony for diseases, before prescriptions were made by doctors. In addition, the author wants to invite readers, especially young people, to get to know identity through cultural corridors.